2020
DOI: 10.25259/sni_487_2020
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral occipital metastases: Visual deficits and management considerations

Abstract: Background: Metastases to the bilateral occipital lobes pose a difficult clinical scenario due to risk of debilitating visual loss. We sought to characterize clinical outcomes following different treatment modalities to help guide management in this challenging situation. Methods: We retrospectively reviewed brain metastases patients treated at a single institution between 2008 and 2017 and assessed visual symptoms before and after treatment, the tumor and peritumoral edema volumes before treatment, and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Xiao et al reported improvement in visual symptoms and papilledema in patients with ventriculomegaly after surgical treatment with ventriculostomy to relieve the IICP ( 19 ). In addition, visual symptoms improved in 70% of the patients with occipital lobe metastasis after a combination of surgery and radiation therapy ( 20 ). Galal et al identified indicators that predict a better visual outcome post-operatively, including duration of symptoms less than 1 year, partial visual deficits, tumor size less than 3 cm in maximum diameter, and a lesser degree of stretch and compression of the optic apparatus ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al reported improvement in visual symptoms and papilledema in patients with ventriculomegaly after surgical treatment with ventriculostomy to relieve the IICP ( 19 ). In addition, visual symptoms improved in 70% of the patients with occipital lobe metastasis after a combination of surgery and radiation therapy ( 20 ). Galal et al identified indicators that predict a better visual outcome post-operatively, including duration of symptoms less than 1 year, partial visual deficits, tumor size less than 3 cm in maximum diameter, and a lesser degree of stretch and compression of the optic apparatus ( 17 ).…”
Section: Discussionmentioning
confidence: 99%